(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Businesses all over the world are noticing a shift in the economy refocusing their efforts one-commerce. The ecommerce industry’s rapid growth has increased the competition among marketers.Customer retention strategies have long been recognised as critical to the long-term success of abusiness. The study’s goals were to learn more about e-commerce businesses’ customer retentionstrategies. A convenience sampling method was used in the study, which was descriptive in nature. Thesurvey participants were given a well-structured questionnaire. There were two sections to the surveyone collected demographic data, other sought to uncover tactics for keeping customers loyal. Excel SPSS were used to conduct statistical analysis, or the data were analyzed in tabular form withexplanations.